2020
DOI: 10.1088/1742-6596/1629/1/012100
|View full text |Cite
|
Sign up to set email alerts
|

Application analysis of Iwrite platform in English writing teaching in higher vocational education

Abstract: This paper first analyzes the current obstacles of English writing and teaching under the traditional writing teaching model. Then based on constructivism and input-out theory, relying on Iwrite, we conducted a one-year experimental teaching. The experimental class adopts the online and offline hybrid writing teaching based on Iwrite, while only traditional offline teaching is adopted in control class. By comparing the results of pretest and post-test, students’ scores of the experimental class increased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Pigai and iWrite are the most extensively used two systems locally, and their performance and validity of them were studied thoroughly. Studies showed that both systems had shortcomings in scoring and providing feedback for learners (Qian et al, 2019;Yan, 2019;Wu, 2020). Aim Writing is another new AES system developed by Microsoft Research of Asia (MSRA), and it was launched in China in late 2019.…”
Section: Aes Feedbackmentioning
confidence: 99%
“…Pigai and iWrite are the most extensively used two systems locally, and their performance and validity of them were studied thoroughly. Studies showed that both systems had shortcomings in scoring and providing feedback for learners (Qian et al, 2019;Yan, 2019;Wu, 2020). Aim Writing is another new AES system developed by Microsoft Research of Asia (MSRA), and it was launched in China in late 2019.…”
Section: Aes Feedbackmentioning
confidence: 99%
“…Pigai and iWrite are the most extensively used two systems locally, and their performance and validity of them were studied thoroughly. Studies showed that both systems had shortcomings in scoring and providing feedback for learners (Qian et al, 2019;Wu, 2020;Yan, 2019). Aim Writing is another new AES system developed by Microsoft Research of Asia (MSRA).…”
Section: Aes Feedbackmentioning
confidence: 99%